Influence of Parental Involvement on Learning Outcomes at Public Early Childhood Centres in Nairobi City County, Kenya - Nyakundi, Orpha; Nyagah, Grace; Kalai, Jeremiah; Munayi, Simon (Journal of Education and Practice, 2020)
Purpose: Parental support is essential in achieving pupils' learning outcomes. The purpose of this article is to discuss how parental involvement in pupils' learning programmes influences pupils' learning outcomes. The study was conducted in public Early Childhood centres in Nairobi City County, Kenya, to investigate the influence of parental involvement in pupils' learning programmes on children's learning outcomes. The problem is that, despite that parents have a responsibility and an influence in the education of their children, not all parents are involved in the learning programmes at the early childhood centres. The objectives of the study were to assess the extent of parental involvement in pupils' learning programmes and to determine the influence of parental involvement in children's learning programmes on learning outcomes. Methodology: The study employed descriptive survey targeting the 21 public stand-alone early childhood education centres, 2243 children aged 3-5 years, 21 head teachers and all teachers at the learning centres. Quantitative and qualitative data was collected by using structured interview schedules for head teachers, closed questionnaires for teachers and document analysis guide to process pupils' learning outcomes (performance). Records of Pupils of PP1 and PP2 levels from each centre were simple randomly sampled for review. By purposive sampling, 48 teachers were sampled, at least one teacher for each of the levels from the 21 institutions. The study employed, means, percentages and the coefficients in the analysis of the data. Findings: The study revealed that 38.1 percent of the learning centres had parents who gave less than 50 percent of the expected support and that centres that involved parents in the learning programmes had higher learning outcomes. The conclusion is that parental involvement in the education of their children leads to high learning outcomes. Unique contribution to theory, practice and policy: The study recommended that The County Government should develop and implement a policy to support establishment and enforcement of a framework through which parents can work in partnership with the teachers at the learning centres. There is need for government instituted structures for sensitization of the parents on their role in the education of their children.